Family Resilience in Urban Extreme Poverty - Ramadhana, Maulana Rezi (Journal of Family Sciences, 2024)
The impact of poverty causes pressure that weakens family resilience. Although measurements of family resilience are available, there are not many up-to-date measures for urban poor families in Indonesia. The purpose of this study is to describe the profile of family resilience and the conditions of vulnerability of extreme urban poor families. The research subjects were the heads of families (N=416) spread across five sub-districts in the city of Bandung, with the highest number of poverties, where most of the subjects worked as daily laborers. The measurement uses a scale of family resilience through four dimensions: the quality of physical, economic, psychological, social, and family structure as demographic resilience. Data were analyzed with descriptive and correlational statistics using JASP 0.15. The results show that poor families have a level of fulfillment of family resilience qualities of 16.5 percent (12.62 percent on the dimensions of physical endurance, 12.46 percent on the economic dimension, 17.33 percent on the psychological dimension and 19.95 percent on the social dimension). Several dimensions have a significant positive relationship, with the highest level on the relationship between dimensions of physical and economic resilience (r=.768). Six conditions of vulnerability were found, namely related to job instability and income that is less than needed, environmental cleanliness and insufficient food consumption, misunderstanding of family goals, and lack of gratitude for conditions. The research findings show two sub-dimensions in each dimension of social resilience and psychological resilience. Suggestions and implications are directed at recommendations for urban extreme poverty alleviation programs and optimizing family quality programs, especially aspects of independence.